Influência da ação do tráfego no custo de construção e restauração de pavimentos asfálticos - Klamt, Rodrigo André (2014)
It is known that traffic in Brazil has increased significantly in recent years due to high dependence on road transportation. In addition, commercial vehicles come to market with new settings, with more axles and greater cargo capacity; also as a function of legislation, that currently tolerates an overload of 10% per axle, when the vehicle is within the 5% of limit for the total gross weight (TGW). Consequently, there has been a considerable increase in the degradation of our road network. In this context, the present study aims to evaluate effects caused by the action of traffic in the cost of flexible pavements, focusing on aspects related to growth rate and excess load. Thus, the projection of traffic volume during a given period of time should express the current growth rates of cargo, so, the commercial vehicles; and it was also examined, if these indices are correlated with the Brazilian GDP and with the truck sales in the country. In another step, it was proposed a case study by selecting one of the toll plazas of the study to perform the sizing of the pavement by using DNIT method and mechanistic-empirical methods in order to analyze the influence of overloading in commercial vehicles in the design and in the cost of construction of the asphalt floors. For the same case study, it was performed the sizing and the calculation of the cost of paving restoration. Thus, in this study, it was concluded that the real traffic growth rate in the regions investigated are considerably above the one proposed by DNIT, which is 3.00%. The average growth rate of the study was 7.16%. The correlation between the rate of growth, the GDP and the truck sales was weak. The influence of overloading in the number N was in the order of 23.11% if compared the scenarios from the minor to the larger load. As for the DNIT method for different values of subgrade CBR (4%, 10% and 16%) the thickness of coating was the same for all loads, reaching the upper limit of the method in 12.5cm. By the mechanistic-empirical analysis, the one that showed to be more conservative was the comparison of the methods FHWA x Asphalt; with higher coating thickness (up to 16 cm) depending on fatigue and permanent deformation, while setting a higher execution cost, which increases the higher is the overload on commercial vehicles, being the maximum difference of cost depending on the cargo, in the order of R$ 158,231.00 (6.18%) per kilometer of pavement. As for the restoration, it was possible to realize that the increase in percentage of commercial vehicles and overloading in these vehicles causes a decrease in the allowable deflection and, consequently, an increase in thickness of reinforcement. It was observed a need of strengthen in all scenarios of loading for all characteristic deflections studied. The highest values of reinforcement thickness were for Dc equal to 125 (10−2mm) with 19 cm. The difference in the cost in function of the loading was R$ 51,450.00 (4.95%) per kilometer of pavement. The survey allowed obtain real parameters for subsequent interventions on existing roads; as well as to support new designs of road engineering.